Trade in Trash: A Political Economy Approach - James H. Cassing; Ngo Van Long (Center for Economic Studies and Ifo Institute (CESifo), 2020)
We study how the opportunity to trade in trash might influence the equilibrium outcome when the tax on the externality is determined by a political economy process. In our model, individuals have heterogeneous preferences for environmental quality, and there is a leakage when funds are transferred from the pressure groups to the politicians. When hard-core environmentalists and capitalists are organized interest groups while moderate environmentalists are not organized, we find that the politically chosen tax on the externality is below the optimal Pigouvian level. The opportunity to export waste in unlimited quantities, but at a price, is not the environmentalists' panacea and does not eliminate political social tension and suboptimal results.
Keywords: F18; D72; 330; trade in trash; interest groups; externalities; environmental lobby; political economy; trade and environment